Response-retrieval in identity negative priming is modulated by temporal discriminability - Mittner, Matthias; Behrendt, Jörg; Menge, Uwe; Titz, Cora; Hasselhorn, Marcus (Frontiers in Psychology, 2014)
Reaction times to previously ignored information are often delayed, a phenomenon referred to as negative priming (NP). Rothermund, Wentura & De Houwer (2005) proposed that negative priming is caused by the retrieval of incidental stimulus-response associations when consecutive displays share visual features but require different responses. In two experiments we examined whether the features (color, shape) that reappear in consecutive displays, or their level of processing (early-perceptual, late-semantic) moderate the likelihood that stimulus-response associations are retrieved. Using a perceptual matching task (experiment 1), negative priming occurred independently of whether responses were repeated or switched. Only when implementing a semantic-matching task (experiment 2), negative priming was determined by response-repetition as predicted by response-retrieval theory. The results can be explained in terms of a task-dependent temporal discrimination process (Milliken et al., 1998): Response-relevant features are encoded more strongly and/or are more likely to be retrieved than irrelevant features.